Butylated hydroxyanisole sebagai Bahan Aditif Antioksidan pada Makanan dilihat dari Perspektif Kesehatan - Fitri, Nyoman (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2014)
Butylated hydroxyanisole (BHA) is widely used since 1947 as antioxidant food additives used to prevent oils, fats and shortenings from oxidative deterioration and rancidity. It has been extensively studied for potential activities and its toxicities. This review summarized experimental studies that had been carried out on animals and humans as well. We also briefly reviewed about its absorptions, metabolisms, excretions and carcinogenicity from health perspective. At present there is sufficient evidence for carcinogenicity of BHA, but there is hardly any indication that BHA is genotoxic. Keywords: Butylated hydroxyanisole, Additive, Ef